AS LUTAS CONTRA A VIOLÊNCIA E A SAÚDE DE MULHERES: APONTANDO CAMINHOS PARA A INTEGRALIDADE - Emmerich, Camila Tobio (2022)
This work arises from an attentive and problematizing look at the Public Policies for Women's Health in Brazil, in the face of the alarming violence to which women have been subjected and which they have denounced. It is questioned, with feminist studies contributions, mainly black and decolonial, about the production of this violence, considering the daily practices that are also present in health policies. The bibliographic review carried out on what is conventionally called "women's health" in the context of public health policies has an important milestone related to the principle of integrality, one of the principles of SUS (BRASIL, 1990) including the publication of the National Policy for Integral Attention to Women’s Health (PNAISM) in 2004. In this sense, when making contact with records of struggles for public health, crossed by interference produced by women's movements and other popular segments, the principle of integrality is highlighted in this research. By questioning hegemonic notions of health, the research problem began to revolve around the ways in which the issue of gender violence has appeared as a health issue, focusing mainly on its effects on women (cis and trans, as well as of other gender dissidents). Starting from a cartographic research direction, semi-structured interviews were carried out with professionals working in the Primary Health Care Policy and others in a service called the Violence Prevention and Health Promotion Nucleus in Vitória/ES (NUPREVI), seeking to explore the notions of integrality in the interface with gender violence and its confrontation, located in the field of health. Integrality, in the conversations, asserted itself as a deviceprinciple for expanding and complexifying issues, such as the intervention richness produced in intersectoral partnerships, as well as in other strategies. Finally, we indicate a policy to combat violence against women with recent consolidation milestones and the need for it to be strengthened in its public and integral dimension.